UTILIZING FLASHCARDS TO IDENTIFY PHONOLOGICAL ERRORS AND ENHANCE LEARNING ENGAGEMENT AMONG STUDENTS WITH INTELLECTUAL DISABILITIES - Wijaya, Karina Aprisyahila; Nanda, Deri Sis; Susanto, Susanto (Journal of English Language and Culture, 2025)
Education is a right for every individual. For students with mental disorders, teaching English poses a unique challenge that requires teachers to find effective teaching media for vocabulary instruction. This study aims to identify phonological errors of students with intelectual disabilities learning vocabulary and explore how to teach vocabulary to students with intelectual disabilities using flashcards the research employs a qualitative approach with descriptive analysis, involving observation and auditory analysis to identify four voice recordings from students with different intelectual disabilities. The results reveal that students who experienced ADHD and communication disorder showed good engagement during the learning process, but encountered pronunciation errors. Meanwhile, students with autism and slow learning experienced difficulties in both participating in learning activities and pronunciation. These difficulties are caused by intelectual disabilities affecting their socialization abilities and leading to learning delays. Based on these findings, it can be said that the use of flashcards is effective as a vocabulary-learning medium for students with mild mental disorders. However, for students with more severe mental disorders, a more authentic approach is required. This is important for educators to understand students’ conditions in determining the appropriate teaching media.